GALLERY WALK TECHNIQUE IN ENHANCING READING COMPREHENSION IN RECOUNT TEXT OF SENIOR HIGH SCHOOL STUDENTS IN MEDAN - Harland, Nadynne Athaya; Salmiah, Maryati (Indonesian EFL Journal, 2024)
The purpose of this study is to evaluate how well senior high school students' reading comprehension is improved by the Gallery Walk approach. This study uses an experimental group design, control pretest and posttest, and quantitative quasi-experimental methodology. The sample size for this research consisted of a total of 60 high school students from two classes: 30 students in the experimental class (class X-1) and 30 students in the control class (class X-2). The final results of the experimental class that used the Gallery Walk strategy showed a higher level of reading comprehension, namely 53.33% compared to the control class, only 16.67% of students who succeeded in the test. Statistical analysis revealed significant improvements in post-test scores among students in the experimental group, indicating the efficacy of the Gallery Walk technique. Validity and reliability tests confirmed the robustness of the research instrument. The findings suggest that the Gallery Walk technique fosters active learning, develops critical thinking skills, and enhances reading comprehension abilities among high school students. This study contributes valuable insights into innovative teaching strategies for improving reading comprehension in English education. Beyond the intervention itself, any potential contributing variables to the observed differences between the experimental and control groups should be taken into account when interpreting the results.Keywords: Gallery Walk; Pre-test; Post-test; Reading Comprehension; SHS students.